The Correlation Between Teaching Style and Learning Interest in Pancasila Education Among Second-Grade Students at Sabilina Islamic Elementary School - Niken Widy Astuti; Lelly Qodariah (FKIP - Universitas Riau, 2026)
Learning interest supports students’ attention and participation in elementary classrooms, while Pancasila Education requires engaging instructional approaches to encourage involvement. This study aimed to determine the relationship between teacher teaching style and student learning interest in Pancasila Education among second-grade students at Sabilina Islamic Elementary School. A quantitative correlational design was employed with 51 second-grade students selected using saturated sampling. Data were collected using a three-point Likert-scale questionnaire consisting of 31 trial items. Following validity testing, 18 items were retained, comprising six items measuring teacher teaching style and twelve measuring student learning interest. The instrument demonstrated high internal consistency, with Cronbach’s alpha of .817 across the 31 trial items. Data were analyzed using descriptive statistics, the Kolmogorov-Smirnov normality test, Pearson product-moment correlation, and simple linear regression. The results showed a strong positive and significant relationship between teacher teaching style and student learning interest (r = .704, p < .001, N = 51). The regression model was significant, F(1, 49) = 48.064, p < .001, with R² = .495, indicating that teaching style accounted for 49.5% of the variance in learning interest. These findings suggest that interactive teaching practices may support students’ attention, engagement, and participation in Pancasila Education.